2009
DOI: 10.1590/s0103-50532009000600026
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil composition of Croton palanostigma Klotzsch from north Brazil

Abstract: Os óleos essenciais das folhas, ramos finos, galhos, cascas do caule e frutos de Croton palanostigma foram analisados por CG e CG-EM. Os componentes principais determinados no óleo das folhas foram linalol (25,4%), (E)-cariofileno (21,0%), metileugenol (17,2%) e b-elemeno (6,0%); no óleo dos ramos finos foram a-pineno (41,4%), limoneno (29,0%), sabineno (11,5%) e b-pineno (5,7%); no óleo dos galhos foram metileugenol (24,1%), (E)-metilisoeugenol (15,3%), a-pineno (11,2%) e (E)-cariofileno (8,5%); no óleo das c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
2
5
0
4
Order By: Relevance
“…Brine shrimp eggs (Maramar) were hatched in artificial salt water (1.0 L of mineral water and 33 g of marine crude NaCl) and used after 24 h applying the modified literature method (Brasil et al, 2009;Parra et al, 2001). Experiments were conducted along with positive control and negative control and different concentrations (0.02; 0.04; 0.06; 0.12; 0.23; 0.25; 0.47; 0.50; 1.0; 5.0; 10.0; 25.0; 50.0 and 100 µg/mL to oil) in a set of three tubes per dose.…”
Section: Brine Shrimp Bioassaymentioning
confidence: 99%
“…Brine shrimp eggs (Maramar) were hatched in artificial salt water (1.0 L of mineral water and 33 g of marine crude NaCl) and used after 24 h applying the modified literature method (Brasil et al, 2009;Parra et al, 2001). Experiments were conducted along with positive control and negative control and different concentrations (0.02; 0.04; 0.06; 0.12; 0.23; 0.25; 0.47; 0.50; 1.0; 5.0; 10.0; 25.0; 50.0 and 100 µg/mL to oil) in a set of three tubes per dose.…”
Section: Brine Shrimp Bioassaymentioning
confidence: 99%
“…In addition to differences in essential oil constitution among distinct species of the genus Croton, several authors have demonstrated distinct essential oil compositions of different tissues from the same species (Brasil et al, 2009;Lima et al, 2010;Morais et al, 2006;Neves and Camara, 2012). In general, the essential oils of Brazilian Croton species present mono and sesquiterpenes as major components, with the exception of C. zehntneri, in which the phenylpropanoids eugenol and anetol predominate (Craveiro et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Compostos considerados bioativos apresentam atividade insetífuga, antimicrobiana, antiviral, antiúlcera, gastroprotetora e antitumoral (Maciel et al, 1998;Fattorusso et al, 2002;Campos et al, 2010). Relatos sobre ocorrência de clerodanos em Croton (principalmente furano-clerodanos) são bastante comuns tendo registro em C. cajucara (Maciel et al, 1998;Grynberg et al, 1999;Souza et al, 2006;Campos et al, 2010), C. draco (Murillo et al, 2001;Deepika-Gupta et al, 2008), C. eluteria (Fattorusso et al, 2002), C lechleri (De Marino et al, 2008), C. membranaceous (Bayor et al, 2009), C. oblongifolius (Youngsa et al, 2007, C. palanostigma (Socorro et al, 2004;Brasil et al, 2009) e C. polyandrus (Araújo-Junior et al, 2005. Nos trabalhos realizados com C. cajucara, um dos diterpenos mais característico é a trans-crotonina, um furano-clerodano bioativo com atividades fungicida (Souza et al, 2006), anti-úlcera (Campos et al, 2010), antitumoral e anti-inflamatória (Grynberg et al, 1999).…”
Section: Fórmula MMunclassified
“…Esta substância já foi descrita em C. sonderianus (Amaral et al, 2004), C. oligandrum (Agnaniet et al, 2006), C. zehntneri, C. nepetaefolius, C. argyrophylloides (Lima et al, 2006;, C. urucurana (Simionatto et al, 2007), C. palanostigma (Brasil et al, 2009) e C.zambesicus (Usman et al, 2009) sendo componente majoritário para C. oligandrum e C. sonderianus. Nas espécies estudadas o cineol foi detectado em altas concentrações em folhas de C. ericoides (24,15% do total identificado), C. dusenii (16,4%), C. linearifolius (26,87%) e C. muellerianus (23,87%) (Tabela 05).…”
unclassified
See 1 more Smart Citation